Citrus wastes: A valuable raw material for biological applications - Tabisa Diniso, Ayodeji O. Oriola, Jerry O. Adeyemi, Gugulethu M. Miya, Yiseyon S. Hosu, Opeoluwa O. Oyedeji, Simon K. Kuria, Adebola O. Oyedeji (Journal of Applied Pharmaceutical Science, 2024)
Agricultural wastes have become a worrying concern worldwide due to the increasing demand for more food items brought about by the ever-increasing population growth in recent times. In the quest toward maintaining a sustainable food production process and combating the issues of food security challenges, the accompanying agricultural waste has become a significant environmental concern to life. About 130 million tons of agricultural waste are generated by India and China alone yearly, which is a worrying amount by just two nations, most of which are not adequately managed and disposed of, posing severe threats to the environment and humans. Citrus is a prominent example of these agricultural wastes that have contributed substantially over the years. This is because citrus accounts for nearly a fifth of the total cultivars industrially processed into food materials, leading to a significant agricultural waste of about 120 million tons worldwide. The industrialization of citrus production due to their continuous usage as different dietary materials and nutritional benefits has led to this massive waste because only 45% of the total fruit weight is being harnessed. Nevertheless, these waste materials, such as peels, leaves, and seeds, have different phytochemicals such as naringin and hesperidin, which is indicative of their usefulness as biological agents for pharmaceutical, cosmeceutical, nanobiotechnology, food, and agricultural applications. Hence, this report briefly highlights the progress made in using citrus waste materials as biological agents by identifying some significant bioactive materials that have been found useful for various biological functions.
Keywords: Citrus wastes, agriculture, phytochemicals, biological applications